Vpliv družbenih omrežij na rabo paremioloških enot - Jakop, Nataša (Slavistična revija, 2022)
Paremiological units (paremias) are used in contemporary Slovenian in various types of texts in social networks. This article analyzes factors that impact their use in social networks. The empirical analysis is limited to paremiological units with the component kruh (Eng. bread). The parameters taken into account in the analysis are: type and specificities of the social network, general familiarity with or the frequency of use of paremiological units in contemporary Slovenian, and the features related to the contextual use of the paremiological genre in the texts of social networks.
Keywords: frazeološka sestavina kruh; Janes corpus; korpus Janes; korpus Pregovori; paremiological genre; paremiological variability; paremiološka variantnost; paremiološki žanr; phraseological component kruh; Proverbs corpus; Slovene; slovenščina